2017
DOI: 10.1177/2048872617715019
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction indicative of outcomes in hospitalized patients with takotsubo syndrome

Abstract: Renal dysfunction is a simple but useful means of predicting complications in hospitalized patients with takotsubo syndrome, especially those with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In Chinese patients with TTS and CKD undergoing primary percutaneous coronary intervention, 30 -day mortality was 4.08%, 1 -year mortality was 7.95%, and renal dysfunction (both CKD [19.7%] and AKI [29.5%]) developed in 49% of patients, whereas in a Korean study by Shin et al, 8 7 of 30 patients with stress -induced cardiomyopathy had renal dysfunction (4 on hemodialysis and 3 with AKI). 16 Other studies on TTS did not assess kidney function, serum creatinine levels, or eGFR.…”
Section: -22mentioning
confidence: 99%
See 1 more Smart Citation
“…In Chinese patients with TTS and CKD undergoing primary percutaneous coronary intervention, 30 -day mortality was 4.08%, 1 -year mortality was 7.95%, and renal dysfunction (both CKD [19.7%] and AKI [29.5%]) developed in 49% of patients, whereas in a Korean study by Shin et al, 8 7 of 30 patients with stress -induced cardiomyopathy had renal dysfunction (4 on hemodialysis and 3 with AKI). 16 Other studies on TTS did not assess kidney function, serum creatinine levels, or eGFR.…”
Section: -22mentioning
confidence: 99%
“…This finding has not been reported by previous studies. [14][15][16][17] Ando et al 16 showed that renal dysfunction in TTS was associated with the development of For commercial use, please contact the journal office at pamw@mp.pl.…”
Section: -22mentioning
confidence: 99%
“…In our previous publication, low BMI proved to be a significant death risk factor during the 3-year observation of patients with TS [7], which prompted us to perform additional analyses in longer follow-up [7]. In recently published papers the BMI value is mainly described as the average value characterising the takotsubo group, or it is used to distinguish the group of obese patients [6,23]. Desai et al [24] stated that obese patients with TS revealed a higher risk of severe complications during the final stage of the disease (sudden cardiac arrest, cardiogenic shock, respiratory failure, necessity to implement devices providing left ventricular hemodynamic support), whereas in-hospital mortality was similar to values observed in the group of patients who were not obese.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several complications during in-hospital course and follow up may occur in TTS with an event rate comparable to that observed in patients with acute coronary syndrome (ACS) [4][5][6][7] . However, both short 8,9 and long-term 6,10 prognosis remain quite heterogeneous in TTS, which supports the need of improved risk stratification in order to identify those patients who may most benefit from intensive in-hospital management and long-term clinical follow-up 11 . Dyspnea at presentation is associated with worse prognosis in ACS 12 , and its assessment was able to improve accuracy of a traditional risk stratification model in these patients 13 .…”
mentioning
confidence: 99%